Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. - Ramalho, Laís V.; López-Fé, Carlos M.; Rueda, José Luis (Zootaxa, 2018)
Diapirs and mud volcanoes (MVs) are formed by the migration and extrusion of fluids and mud to the seafloor, respectively. In the Gulf of Cádiz there are ca. 60 MVs and several diapirs with different environmental conditions and seepage activity. Previous studies, mainly on MVs, have demonstrated that the invertebrate fauna associated with these seafloor structures can be very diverse, including chemosymbiotic species, mostly mollusks and frenulate polychaetes, as well as vulnerable suspension feeders, such as cold-water corals and sponges, among others. Previous studies of the bryozoan fauna in this area have recorded species belonging to 28 families. One of these families is Phidoloporidae, which comprises 27 genera worldwide, including the common Rhynchozoon, Reteporellina, and Reteporella. In the present study, two species belonging to Reteporella are redescribed, and a new species is described from diapirs and MVs on the shelf and slope of the Gulf of Cádiz. The samples were collected during several oceanographic expeditions carried out by the Instituto Español de Oceanografia. This genus is well represented in the NE Atlantic Ocean and the Mediterranean Sea, and our study extends its occurrence on MVs and diapirs fields of the Gulf of Cádiz.